5.
Part 2
The principal real square root is also 5.
Simplify. Square Root 25
Part 1
The principal square root is
83 answers
Evaluate the square root. Square root 100/121
Question content area bottom
Part 1
Square Root 100/121 =
Question content area bottom
Part 1
Square Root 100/121 =
Square Root 100/121 = 10/11
Evaluate the square root. Square Root 1.69
Question content area bottom
Part 1
Square Root 1.69 =
Question content area bottom
Part 1
Square Root 1.69 =
Square Root 1.69 ≈ 1.3
Without using a calculator, determine between which two consecutive integers the square root lies.
Square Root 31
Question content area bottom
Part 1
< square root 31 < (Simplify your answer.)
Square Root 31
Question content area bottom
Part 1
< square root 31 < (Simplify your answer.)
5 < square root 31 < 6
Choose which group of sets the following number belongs to. Be sure to account for ALL sets.
-8/9
Question content area bottom
Part 1
A.
real numbers, rational numbers
B.
real numbers, irrational numbers
C.
real numbers, rational numbers, natural numbers
D.
rational numbers, natural numbers, integers
E.
irrational numbers, natural numbers
-8/9
Question content area bottom
Part 1
A.
real numbers, rational numbers
B.
real numbers, irrational numbers
C.
real numbers, rational numbers, natural numbers
D.
rational numbers, natural numbers, integers
E.
irrational numbers, natural numbers
A. real numbers, rational numbers
Choose which group of sets the following number belongs to. Be sure to account for ALL sets.
-9
A. Intergers, rational numbers, real numbers
B. intergers, natural numbers, real numbers
C. whole numbers, integers, rational numbers, natural numbers, real numbers
D.whole numbers, integers, irrational numbers, natural numbers, real numbers
-9
A. Intergers, rational numbers, real numbers
B. intergers, natural numbers, real numbers
C. whole numbers, integers, rational numbers, natural numbers, real numbers
D.whole numbers, integers, irrational numbers, natural numbers, real numbers
B. integers, natural numbers, real numbers
Choose which set or sets the following number belongs to. Be sure to account for ALL sets.
- Square Root 8
Question content area bottom
Part 1
A.
rational numbers, real numbers
B.
irrational numbers, real numbers
C.
irrational numbers
D.
rational numbers
E.
real numbers
- Square Root 8
Question content area bottom
Part 1
A.
rational numbers, real numbers
B.
irrational numbers, real numbers
C.
irrational numbers
D.
rational numbers
E.
real numbers
B. irrational numbers, real numbers
Choose the property illustrated by the following statement.
(7 • Y) • 5 = 7 • (y • 5)
associative property of multiplication
B.
commutative property of multiplication
C.
distributive property
D.
identity element of multiplication
(7 • Y) • 5 = 7 • (y • 5)
associative property of multiplication
B.
commutative property of multiplication
C.
distributive property
D.
identity element of multiplication
A. associative property of multiplication
Name the property that the following statement illustrates.
64 + 4 = 4 + 64
Question content area bottom
Part 1
Choose the correct property below.
A.
Commutative property of addition
B.
Associative property of addition
C.
Associative property of multiplication
D.
Identity property of multiplication
E.
Commutative property of multiplication
F.
Identity property of addition
64 + 4 = 4 + 64
Question content area bottom
Part 1
Choose the correct property below.
A.
Commutative property of addition
B.
Associative property of addition
C.
Associative property of multiplication
D.
Identity property of multiplication
E.
Commutative property of multiplication
F.
Identity property of addition
A. Commutative property of addition
Name the property that the following statement illustrates.
21 • pi = pi • 21
Question content area bottom
Part 1
Choose the correct property below.
A.
Identity property of multiplication
B.
Commutative property of addition
C.
Associative property of multiplication
D.
Associative property of addition
E.
Identity property of addition
F.
Commutative property of multiplication
21 • pi = pi • 21
Question content area bottom
Part 1
Choose the correct property below.
A.
Identity property of multiplication
B.
Commutative property of addition
C.
Associative property of multiplication
D.
Associative property of addition
E.
Identity property of addition
F.
Commutative property of multiplication
F. Commutative property of multiplication
The sign at the right shows the costs for a deep-sea fishing trip. How much will the total cost be for 1 adult, 2 children, and 1 senior citizen to go on a fishing trip? Use mental math.
DEEP-SEA FISHING
Adults
Children (12 & under)
Seniors (65 & up)
$21
$15
$19
The total cost will be $ [ ]
DEEP-SEA FISHING
Adults
Children (12 & under)
Seniors (65 & up)
$21
$15
$19
The total cost will be $ [ ]
The total cost will be $21 + $15 + $15 + $19 = $70.
Simplify by using the associative property of multiplication.
8(9y)
8(9y)
By using the associative property of multiplication, we can simplify 8(9y) as follows:
8(9y) = (8 * 9) * y = 72y
8(9y) = (8 * 9) * y = 72y
Use the commutative and associative properties as needed to simplify the expression.
(15 + a) + 11
(15 + a) + 11 = (Simplify your answer)
(15 + a) + 11
(15 + a) + 11 = (Simplify your answer)
Using the associative property, we can remove the parentheses:
(15 + a) + 11 = 15 + a + 11
Using the commutative property, we can rearrange the order of addition:
15 + a + 11 = 15 + 11 + a
Simplifying the addition:
15 + 11 + a = 26 + a
(15 + a) + 11 = 15 + a + 11
Using the commutative property, we can rearrange the order of addition:
15 + a + 11 = 15 + 11 + a
Simplifying the addition:
15 + 11 + a = 26 + a
Use deductive reasoning to tell whether the statement shown below is true or false. If it is true, indicate which property or properties of real numbers are needed to show the expressions are equivalent.
For all real numbers r, s, and t, (r • s) • t=t (s • r)
Select the correct answer below.
A.
The statement is true. The expressions can be shown to be equivalent using only the Associative Property of Multiplication.
B.
The statement is true. The expressions can be shown to be equivalent using both the Commutative Property of Multiplication and the Associative Property of Multiplication.
C.
The statement is true. The expressions can be shown to be equivalent using only the Commutative Property of Multiplication.
D.
The statement is false.
For all real numbers r, s, and t, (r • s) • t=t (s • r)
Select the correct answer below.
A.
The statement is true. The expressions can be shown to be equivalent using only the Associative Property of Multiplication.
B.
The statement is true. The expressions can be shown to be equivalent using both the Commutative Property of Multiplication and the Associative Property of Multiplication.
C.
The statement is true. The expressions can be shown to be equivalent using only the Commutative Property of Multiplication.
D.
The statement is false.
C. The statement is true. The expressions can be shown to be equivalent using only the Commutative Property of Multiplication.
Add.
11 + (-9)
11+ (-9) =
11 + (-9)
11+ (-9) =
11 + (-9) = 2
Add.
-7 + (-6)
-7 + (-6) =
-7 + (-6)
-7 + (-6) =
-7 + (-6) = -13
Subtract. -12 - 4
-12 - 4 =
-12 - 4 =
-12 - 4 = -16
Subtract.
11 - (-16)
11 - (-16) =
11 - (-16)
11 - (-16) =
11 - (-16) = 27
A commercial jet liner hits an air pocket and drops 262 feet. After climbing 157 feet, it drops another 156 feet. What is its overall vertical change?
Question content area bottom
Part 1
The jet's overall vertical change is [ ] feet.
Question content area bottom
Part 1
The jet's overall vertical change is [ ] feet.
The jet's overall vertical change is -261 feet.
Multiply.
Question content area bottom
Part 1
2(-1.6)
2(-1.6) = [ ] (Type an integer or a decimal.)
Question content area bottom
Part 1
2(-1.6)
2(-1.6) = [ ] (Type an integer or a decimal.)
2(-1.6) = -3.2
Simplify the numerical expression. (- 0.2)^2
The simplified form is [ ] (Type an integer or a decimal.)
The simplified form is [ ] (Type an integer or a decimal.)
The simplified form is 0.04.
Simplify. - Square Root 9
Question content area bottom
Part 1
The answer is [ ]
Question content area bottom
Part 1
The answer is [ ]
The answer is -3.
Evaluate.
-125 ÷ 5
-125 ÷ 5 =
-125 ÷ 5
-125 ÷ 5 =
-125 ÷ 5 = -25
A farmer has 180 bushels of apples for sale at a farmer's market. He sells an average of 16 1/8
bushels each day. After 6 days, what is the change in the total number of bushels the farmer has for sale at the farmer's market?
bushels each day. After 6 days, what is the change in the total number of bushels the farmer has for sale at the farmer's market?
To find the change in the total number of bushels the farmer has for sale after 6 days, we need to calculate the total number of bushels sold in 6 days and subtract it from the initial number of bushels.
Total number of bushels sold in 6 days = (16 1/8) * 6
To simplify the calculation, let's convert the mixed number to an improper fraction:
16 1/8 = (8 * 16 + 1) / 8 = 129/8
Now, we can calculate the total number of bushels sold:
Total number of bushels sold in 6 days = (129/8) * 6 = 774/8 = 96.75
Finally, we can find the change in the total number of bushels:
Change in the total number of bushels = 180 - 96.75 = 83.25
Therefore, the change in the total number of bushels the farmer has for sale at the farmer's market after 6 days is 83.25 bushels.
Total number of bushels sold in 6 days = (16 1/8) * 6
To simplify the calculation, let's convert the mixed number to an improper fraction:
16 1/8 = (8 * 16 + 1) / 8 = 129/8
Now, we can calculate the total number of bushels sold:
Total number of bushels sold in 6 days = (129/8) * 6 = 774/8 = 96.75
Finally, we can find the change in the total number of bushels:
Change in the total number of bushels = 180 - 96.75 = 83.25
Therefore, the change in the total number of bushels the farmer has for sale at the farmer's market after 6 days is 83.25 bushels.
A farmer has 180 bushels of apples for sale at a farmer's market. He sells an average of 16 1/8
bushels each day. After 6 days, what is the change in the total number of bushels the farmer has for sale at the farmer's market?
Write a signed number representing the change in the total number of bushels the farmer has for sale.
(Type an integer, proper fraction, or mixed number.)
bushels each day. After 6 days, what is the change in the total number of bushels the farmer has for sale at the farmer's market?
Write a signed number representing the change in the total number of bushels the farmer has for sale.
(Type an integer, proper fraction, or mixed number.)
After 6 days, the farmer sells a total of 16 1/8 * 6 = 97/2 = 48.5 bushels.
To calculate the change in the total number of bushels, we subtract the number of bushels sold from the initial number of bushels:
Change in total number of bushels = 180 - 48.5 = 131.5
Therefore, the change in the total number of bushels the farmer has for sale is 131.5 bushels.
To calculate the change in the total number of bushels, we subtract the number of bushels sold from the initial number of bushels:
Change in total number of bushels = 180 - 48.5 = 131.5
Therefore, the change in the total number of bushels the farmer has for sale is 131.5 bushels.
The formula F = 9/5C + 32 changes a temperature reading from the Celsius scale C to the Fahrenheit scale F. What is the temperature measured in degrees Fahrenheit when the Celsius temperature is -15°C?
The temperature is [ ] °F (Type an integer or a fraction.)
The temperature is [ ] °F (Type an integer or a fraction.)
To find the temperature in degrees Fahrenheit when the Celsius temperature is -15°C, we can use the formula F = (9/5)C + 32.
Substituting -15 for C in the formula:
F = (9/5)(-15) + 32
F = -135/5 + 32
F = -27 + 32
F = 5
Therefore, the temperature measured in degrees Fahrenheit when the Celsius temperature is -15°C is 5°F.
Substituting -15 for C in the formula:
F = (9/5)(-15) + 32
F = -135/5 + 32
F = -27 + 32
F = 5
Therefore, the temperature measured in degrees Fahrenheit when the Celsius temperature is -15°C is 5°F.
A parachutist's elevation changes by -110 ft in 10 seconds. What is the change in the parachutist's elevation each second?
Her elevation changes [] feet each second.
Her elevation changes [] feet each second.
To find the change in the parachutist's elevation each second, we divide the total change in elevation (-110 ft) by the number of seconds (10):
Change in elevation each second = -110 ft / 10 = -11 ft
Therefore, the parachutist's elevation changes by 11 feet each second.
Change in elevation each second = -110 ft / 10 = -11 ft
Therefore, the parachutist's elevation changes by 11 feet each second.
Identify the terms as like or unlike.
5r, -10r^2
Choose the correct answer.
The terms are like terms.
The terms are unlike terms.
5r, -10r^2
Choose the correct answer.
The terms are like terms.
The terms are unlike terms.
The terms are unlike terms.
Use the distributive property to rewrite this expression.
5(p + 9)
5(p + 9) =
5(p + 9)
5(p + 9) =
5(p + 9) = 5p + 45
Use the distributive property to write the expression without parentheses.
7(2a-5)
7(2a - 5) = [ ] (Simplify your answer.)
7(2a-5)
7(2a - 5) = [ ] (Simplify your answer.)
7(2a - 5) = 14a - 35
Write the fraction below as a sum or difference.
7 x + 2 / 3
7 x + 2 / 3 = [ ] (Simplify your answer. Use integers or fractions for any numbers in the expression.)
7 x + 2 / 3
7 x + 2 / 3 = [ ] (Simplify your answer. Use integers or fractions for any numbers in the expression.)
The fraction 7x + 2/3 cannot be simplified further as a sum or difference.
Write the fraction below as a sum or difference.
7 x 2 + / 3
7 x 2 + / 3 = [ ] (Simplify your answer. Use integers or fractions for any numbers in the expression.)
7 x 2 + / 3
7 x 2 + / 3 = [ ] (Simplify your answer. Use integers or fractions for any numbers in the expression.)
7 x 2 + / 3 cannot be written as a sum or difference since it is not a valid expression. There seems to be a missing operand or operation in the expression.
Write the fraction below as a sum or difference.
8 - 15x
_____
5
8 - 15x
_____
5 =
8 - 15x
_____
5
8 - 15x
_____
5 =
8 - 15x
_____
5
= 8/5 - (15x)/5
= 8/5 - 3x
= (8 - 3x)/5
Therefore, the fraction 8 - 15x / 5 can be written as the sum (8 - 3x) / 5.
_____
5
= 8/5 - (15x)/5
= 8/5 - 3x
= (8 - 3x)/5
Therefore, the fraction 8 - 15x / 5 can be written as the sum (8 - 3x) / 5.
Use the distributive property to write the expression without parentheses.
- (2x + 5)
- (2x + 5) = [ ] (Simplify your answer.)
- (2x + 5)
- (2x + 5) = [ ] (Simplify your answer.)
- (2x + 5) = -2x - 5
Use the distributive property to write an equivalent expression.
- (3x - 9)
- (3x - 9) = [ ]
- (3x - 9)
- (3x - 9) = [ ]
To write an equivalent expression using the distributive property, we distribute the negative sign to each term inside the parentheses:
- (3x - 9) = -3x + 9
- (3x - 9) = -3x + 9
You buy 50 of your favorite songs from a Web site that charges $0.99 for each song. What is the cost of 50 songs? Use mental math.
The total cost of 50 songs is $ [ ]
(Simplify your answer.)
The total cost of 50 songs is $ [ ]
(Simplify your answer.)
The total cost of 50 songs is $0.99 * 50 = $49.50.
Question content area top
Part 1
Simplify the algebraic expression.
4x + 7x
4x + 7x = [ ]
Part 1
Simplify the algebraic expression.
4x + 7x
4x + 7x = [ ]
4x + 7x = 11x
Simplify the algebraic expression by combining like terms.
-5x^2 + 16x^2
-5x^2 + 16x^2 = [ ] (Simplify your answer.)
-5x^2 + 16x^2
-5x^2 + 16x^2 = [ ] (Simplify your answer.)
-5x^2 + 16x^2 = 11x^2
Write an expression in simplified form for the area of the rectangle.
3x+4 5
Area = [ ]
3x+4 5
Area = [ ]
Area = (3x + 4) * 5 = 15x + 20
Simplify the expression.
3b ^ c ^ 2 + 6b^2 c^4 - 4b^2 c ^4
3b ^ c ^ 2 + 6b^2 c^4 - 4b^2 c ^4 = [ ]
3b ^ c ^ 2 + 6b^2 c^4 - 4b^2 c ^4
3b ^ c ^ 2 + 6b^2 c^4 - 4b^2 c ^4 = [ ]
To simplify the expression 3b^c^2 + 6b^2c^4 - 4b^2c^4, we can combine like terms:
3b^c^2 + (6b^2c^4 - 4b^2c^4)
Simplifying the terms inside the parentheses:
3b^c^2 + 2b^2c^4
Therefore, the simplified form of the expression is 3b^c^2 + 2b^2c^4.
3b^c^2 + (6b^2c^4 - 4b^2c^4)
Simplifying the terms inside the parentheses:
3b^c^2 + 2b^2c^4
Therefore, the simplified form of the expression is 3b^c^2 + 2b^2c^4.
Simplify the expression.
6(4 + t) - 4 (t + 1)
6(4 + t) - 4 (t + 1) = [ ]
6(4 + t) - 4 (t + 1)
6(4 + t) - 4 (t + 1) = [ ]
To simplify the expression 6(4 + t) - 4(t + 1), we can use the distributive property:
6(4 + t) - 4(t + 1) = 6(4) + 6(t) - 4(t) - 4(1)
Simplifying further:
= 24 + 6t - 4t - 4
Combining like terms:
= 2t + 20
Therefore, the simplified form of the expression is 2t + 20.
6(4 + t) - 4(t + 1) = 6(4) + 6(t) - 4(t) - 4(1)
Simplifying further:
= 24 + 6t - 4t - 4
Combining like terms:
= 2t + 20
Therefore, the simplified form of the expression is 2t + 20.
Simplify the expression.
- ( m + 3n - 9)
- ( m + 3n - 9) = [ ]
- ( m + 3n - 9)
- ( m + 3n - 9) = [ ]
To simplify the expression - (m + 3n - 9), we can apply the distributive property:
- (m + 3n - 9) = -m - 3n + 9
Therefore, the simplified form of the expression is -m - 3n + 9.
- (m + 3n - 9) = -m - 3n + 9
Therefore, the simplified form of the expression is -m - 3n + 9.